The influence of promotional costs on third party finds at PT. Bank BRI Syariah Indonesia - Hieronimus Erwin Indrawan; Suci Dwi Purwati; Amalia Tresna Fadhilah; Yudha Febri Al Paksi; Woro Dwi Hartanty (Enrichment : Journal of Management, 2023)
Banks receive a lot of funds from the public in the form of deposits, both in the form of Savings, Deposits, and other forms of savings offered by the Bank through the "Promotion" program carried out by the Bank. This study aims to find a relationship between Promotional Expenses incurred and the amount of Funds received from customers called Third Party Funds (DPK). In this case, as an example, we use data from Bank BRI Syariah Indonesia for the 2016 – 2020 period. statistical analysis of correlation, determination, and regression assisted by the IBM SPSS version 22 program. The results of data processing show an R2 value of 0.038% indicating that Promotional Costs have an effect on Third Party Funds of 0.0038%, the remaining 0.0038% is influenced by other factors that are not present in this study. Meanwhile, the regression equation that is formed is Ŷ = 26,705,681.242 + 203,726X indicating that if promotion costs increase, third party funds will also increase. The F test results obtained a Sig value of 0.133 greater than 0.05 (Sig. > 0.05). Judging from the results of processing the data based on the results of the regression equation, Promotional Costs have a positive effect on Third Party Funds. However, if we look at the results of the R2 value, the effect is only 0.038%, the rest is influenced by other factors outside this study. Meanwhile, if you look at the results of the F test with the Sig. 0.133 is greater than 0.05 (Sig. > 0.05) so the Promotional Costs have no significant effect on Third Party Funds. So it can be concluded that the purpose of Promotional Fees is not to invite customers to save their funds at Bank BRI Syariah Indonesia. This can raise questions for Bank BRISyariah for what purpose the Promotion is carried out.